BIOMARKER ANALYSIS OF MICROBIAL DIVERSITY IN SEDIMENTS OF A SALINE GROUNDWATER SEEP OF SALT BASIN, NEBRASKA - Fang J.; Chan O.; Joeckel R.M.; Huang Y.; Wang Y.; Bazylinski D.A.; Moorman T.B.; Ang Clement B.J. (My University, 2006)
Lipids extracted from sediments in a saline seep in the Salt Basin of Lancaster County, Nebraska included alkanes, alkenes, alkanols, phytol, C27-30 sterols, C30-32 hopanoids, tetrahymanol, glycolipid and phospholipid fatty acids, and lipopolysaccharide hydroxyl fatty acids. Biomarker profiles suggest that the brine seeps of Salt Basin support a microbial ecosystem adapted to a relatively highly saline and sulfidic environment. The phospholipid fatty acid (PLFA) and lipopolysaccharide hydroxyl fatty acid profiles are consistent with the presence of large numbers of sulfate-reducing bacteria (SRB) in black, sulfidic muds surrounding the seeps. In the context of field and laboratory observations, the presence of large amounts of glycolipid fatty acids is attributed to large populations of photosynthetic microorganisms (cyanobacteria, phytoplankton, and purple sulfur bacteria) that likely play important roles in the local cycling of carbon and sulfur. The sterol profile and the detection of polyunsaturated alkenes (C21:6, C21:7, C30:4, and C30:5) implicates microalgae as important contributors of organic matter at the site. Comparatively high concentrations of phytol (58.2 μg g-1 dry wt sediment) record the activity of photosynthetic organisms in the system. The δ13C of phytol (-37.1‰) is compatible with a dominance of microalgae, cyanobacteria, or higher plants and a lesser contribution from phototrophic sulfur bacteria. The presence of various intermediate degradation products of phytol (phytenes and phytadienes) indicates that SRB likely mediate the chemical reduction of phytol in the anaerobic zone. The presence of C30-32 hopanols can be attributed to cyanobacteria and methanotrophs in oxic regions of the water column, whereas bacterivorous ciliates and phototrophic sulfur bacteria living at the chemocline are likely sources of tetrahymanol. The carbon isotopic composition of individual fatty acids and neutral lipids helps to identify source organisms. These microorganisms and others constitute a unique and integrated ecosystem prescribed by the geochemistry of the Salt Basin. © 2006 Elsevier Ltd. All rights reserved.